2020
DOI: 10.1785/0220200147
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Societal Response Captured by Seismic Noise in China and Italy

Abstract: Seismic noise with frequencies above 1 Hz is often called “cultural noise” and is generally correlated quite well with human activities. Recently, cities in mainland China and Italy imposed restrictions on travel and day-to-day activity in response to COVID-19, which gave us an unprecedented opportunity to study the relationship between seismic noise above 1 Hz and human activities. Using seismic records from stations in China and Italy, we show that seismic noise above 1 Hz was primarily generated by the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
46
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 29 publications
6
46
2
Order By: Relevance
“…The weekday noise level strongly re ected the effects of the state of emergency, but the Sunday noise level likely re ected the concern of the people about the COVID-19 as most people continued to avoid non-essential outings even after emergency was lifted. Compared to other countries [12][13][14][15]24 , our results showed a higher reduction for the higher frequency range noise as MeSO-net stations are located in schools and the noise related to school activities is dominant. At frequencies <20 Hz, the reduction in the noise levels was unclear compared to those for higher frequencies because the number of stations that showed a high correlation coe cient was limited.…”
Section: Resultscontrasting
confidence: 66%
See 2 more Smart Citations
“…The weekday noise level strongly re ected the effects of the state of emergency, but the Sunday noise level likely re ected the concern of the people about the COVID-19 as most people continued to avoid non-essential outings even after emergency was lifted. Compared to other countries [12][13][14][15]24 , our results showed a higher reduction for the higher frequency range noise as MeSO-net stations are located in schools and the noise related to school activities is dominant. At frequencies <20 Hz, the reduction in the noise levels was unclear compared to those for higher frequencies because the number of stations that showed a high correlation coe cient was limited.…”
Section: Resultscontrasting
confidence: 66%
“…The large-scale restrictions on human activities during the pandemic also presented a rare opportunity to clearly distinguish anthropogenic seismic noise from ambient seismic noise. Poli et al 12 and Xiao et al 13 compared ambient seismic noise levels before and during the pandemic-related lockdown by using continuous seismic records for Italy and China, and observed a clear decrease in noise level during the lockdown. Poli et al 12 found that the noise level signi cantly reduced in the frequency band 1-10 Hz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periods that are often seismically quiet include weekends, as well as the Christmas and New Year holidays for locations where they are celebrated. Notably, we found a near-global reduction in noise, commencing in China in late January 2020 (26), followed by Italy (26,27), the whole of Europe, and the rest of the world in March to April 2020. This period of reduced noise lasted longer and was often quieter than the Christmas-to-New Year period.…”
mentioning
confidence: 88%
“…For example, this has been done for NO 2 concentrations in urban areas and globally for aerosol content (NASA, 2020a,b), noise (Bui and Badger, 2020), and seismic tremors (Xiao et al, 2020). Also, the impact of lockdown on night sky brightness in Berlin has been studied (Jechow and Hölker, 2020).…”
Section: Introductionmentioning
confidence: 99%